Menilai Kinerja Keuangan Berdasarkan Metode Economic Value Added (EVA): Studi Kasus Pada PT Adaro Energy, Tbk - Widjayanti, Wahyu; Andrianie, Ayu; Afriyeni, Lince; Pratama, Zudya Arswl (Soratekno Publisher, 2024)
This study aims to determine the financial performance using the Economic Value Added (EVA) method in the coal mining industry sector at PT Adaro Energy Tbk, whether it can create positive or negative EVA values ??for shareholders and creditors in the 2020-2022 period. Economic Value Added (EVA) is one method that can measure the economic added value generated by a company after deducting the cost of capital that has been used. This method aims to calculate the economic added value generated from an investment or business decision. The data analysis method in this study is in the form of quantitative data, where the data contains numbers that can be calculated, and secondary data sources consisting of the balance sheet and profit and loss report of PT Adaro Energy Tbk for the 2020-2022 period, annual reports obtained through the company's official website and the Indonesia Stock Exchange (IDX). The methods used for data collection are documentation techniques and literature studies. The results of the study show that PT Adaro Energy Tbk has generated a positive EVA value or EVA> 0 during the 2020-2022 period. EVA > 0, means that the company's management has created and increased economic added value for shareholders, meaning that the company has succeeded in managing its capital efficiently and effectively or in other words, the company provides a higher rate of return than expected by shareholders or generates more profit than its cost of capital.